Penggunaan Model Problem Based Learning Melalui Google Slides untuk Meningkatkan Pemahaman Konsep Matematika pada Materi Regresi - Werluka, Baceria; Ratuanik, Mesak; Laritmas, Endemina O (KAMBOTI: Jurnal Sosial dan Humaniora, 2025)
Technology can act as a communication tool between educators and students, transforming traditional teaching methods into more innovative approaches. For the fourth-semester students in the Mathematics Education Study Program, who struggle to understand mathematical concepts like regression, the proposed solution is using the Problem-Based Learning (PBL) model with Google Slides to enhance learning quality. This study aims to assess the impact of using the PBL model with Google Slides on students' understanding of mathematical concepts. The research uses a descriptive qualitative method to provide an in-depth explanation of how PBL supported by Google Slides can improve students' understanding of regression material. Data were collected through observation, interviews, documentation, tests, field notes, and literature studies. The results showed a 63% improvement in students' understanding of regression concepts. Nine students scored between 70-100 (high category), three students scored between 55-69.9 (medium category), and one student scored below 54 (low category). The integration of PBL with Google Slides proved effective in enhancing students' understanding of regression topics, such as gradient, y-intercept, and regression. This approach is an effective solution for improving students' comprehension of the material.